The organization and conducting of paratriathlon competitions - Водлозеров, Владимир (Slobozhanskyi Herald of Science and Sport, 2017)
Vladimir Vodlozerov Purpose: to analyze the system of the organization and conducting of competitions among paratriathletes concerning compliance with specifics of this sport – the consecutive overcoming of the combined distance by means of different types of physical activity. Material & Methods: the analysis of conditions of the organization and conducting of competitions of paratriathletes in six competitive categories was made on the basis of studying of articles of the UNO Convention on the Rights of physically disabled people, the regulatory base of the international federations of triathlon and Federation of triathlon of Ukraine. Results: the compliance of the organization and conducting of paratriathlon competitions concerning specifics of continuous triathlon with certain modifications of passing of stages of the combined distance by sportsmen with limited physical capacities is revealed. Conclusions: competition rules on paratriathlon, which allow conducting the fair competitive competition in the spirit of fair, competitive and safe rivalry to athletes with different physical deviations, are developed for more active attraction to sports activities, and also for the purpose of removal of discrimination barriers from physically disabled people.